The Study of Mosque Management in Indonesia and Spain: Majority and Minority Muslim Factors - Sukron Kamil; Zakiya Darojat (Insaniyat : Journal of Islam and Humanities, 2021)
This article aims to analyze and compare the management of mosques between two countries; Indonesia, where Muslims are the majority population, and Spain where Muslims are the minority. The research question is summed upon how the Muslims respond to the mosque management in two countries, Indonesia and Spain. Constructed by both research methods, qualitative and quantitative, this article lists mosques in urban areas both in Indonesia and Spain and analyzes several aspects related to mosque management. The number of questionnaires distributed was 100 to Indonesian Muslim communities in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, and Bekasi), and 100 Muslims in the City of Madrid and Sevilla, in Spain. The study found high scores for mosque management in urban Indonesia related to the community's satisfaction with the mosque services either in the social field (as the power of civil society) or in the main service fields (worship/da'wa). Meanwhile, the score for managing mosques in Spain is low. This fact is related to the issue of better access to resources: economic, socio-cultural, and political mosques in Indonesia as they are the majority population. On the other hand, Spanish Muslims often face various obstacles in building mosques, one of them being tied up with the issue of Islamophobia. In conclusion, Mosque management in Indonesia seems better than in Spain both in social services and in worship/da'wah.